2001
DOI: 10.1038/sj.cgt.7700299
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of oncogenic viral interferon regulatory factor (vIRF) of Kaposi's sarcoma–associated herpesvirus by ribozyme-mediated cleavage

Abstract: Kaposi's sarcoma ± associated herpesvirus / human herpesvirus 8 ( KSHV / HHV8 ) has been etiologically associated with several malignancies including Kaposi's sarcoma and primary effusion lymphoma. Oncogenic viral interferon regulatory factor ( vIRF ) encoded by KSHV ORF -K9 is a homologue of cellular interferon regulatory factor ( IRF ) , and has been demonstrated to inhibit type I / II interferon signal transduction and transform NIH3T3 cells through the interactions with IRF -1, IRF -3, and CBP / p300 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Both PPMOs worked efficiently in inhibiting vIRF-1 expression in BCBL-1 cells, indicating that the 5′-UTR is crucial for vIRF-1 translation. Our finding is consistent with previous publications on the inhibition of vIRF-1 by antisense RNA or by the ribozyme [35,36]. KSHV replication was also reduced in KP1-treated PEL cells.…”
Section: Discussionsupporting
confidence: 93%
“…Both PPMOs worked efficiently in inhibiting vIRF-1 expression in BCBL-1 cells, indicating that the 5′-UTR is crucial for vIRF-1 translation. Our finding is consistent with previous publications on the inhibition of vIRF-1 by antisense RNA or by the ribozyme [35,36]. KSHV replication was also reduced in KP1-treated PEL cells.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is highly possible that the stem sequence in the mutant ribozyme can still recognize the survivin mRNA, and inhibit the expression of survivin mRNA by an antisense effect, thus inducing apoptosis. A very similar phenomenon has been reported by Zhang et al 51 It was found in their study that a mutant ribozyme had no cleavage activity in vitro, but exhibited an antisense effect in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to findings on EBV, many reports employing antisense technology proved that HHV-8-related malignancies can also be therapeutically approached, either by silencing viral products [117][118][119] or by targeting cellular genes implicated in the disease pathophysiology.…”
Section: Antisense Oligonucleotidesmentioning
confidence: 69%